2005
DOI: 10.1590/s1415-47572005000500017
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA content and karyotype of Rosewood (Aniba rosaeodora)

Abstract: Rosewood (Aniba rosaeodora Ducke, Lauraceae) is ecologically and economically important to the Amazon region. As a consequence of its economic importance, rosewood populations have been decimated in the Amazon forest. Species of nine genera of the Lauraceae family have characterized karyotypes with n = x = 12 chromosomes in the gametophytic phase but the genus Aniba is one of the least studied Lauraceae genera with a previously undescribed genome. We used cytogenetic techniques to determine that the A. rosaeod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…These techniques allowed the obtention of chromosomes well-spread in the same focus plane, without cytoplasmic background, overlaps or structural deformations. Identical results were obtained in Zea mays Saraiva 1993, 1997), Capsicum annuum (Almeida and Carvalho 2004) and Aniba rosaeodora (Contim et al 2005).…”
Section: Discussionsupporting
confidence: 68%
“…These techniques allowed the obtention of chromosomes well-spread in the same focus plane, without cytoplasmic background, overlaps or structural deformations. Identical results were obtained in Zea mays Saraiva 1993, 1997), Capsicum annuum (Almeida and Carvalho 2004) and Aniba rosaeodora (Contim et al 2005).…”
Section: Discussionsupporting
confidence: 68%
“…The Amazon region represents one of the richest reservoirs of biological diversity on the planet (Confalonieri et al 2014;Gentry 1992), and is considered a biodiversity hotspot that can serve as a potential source of genetic variability for breeding perspectives of crops (Myers et al 2000;Gentry 1992). Rosewood, Aniba rosaeodora Ducke (Lauraceae) has 2n = 24 chromosomes (Contim et al 2005), and is distributed in the Amazon region of Brazil, Guyana, Suriname, Peru, Colombia, and Venezuela (Maia and Mourão 2016). The species is known for its essential oil, which is mainly characterized by a high content of linalool in the leaves and branches (74.4 -81.8%) (Pimentel et al 2018) and in the trunk wood (~ 100%) (Chantraine et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In view of this similarity, both DAPI and PI can be used for flow cytometry analysis of H. salsaparilha. Concurrently, Contim et al (2005) reported similar responses for Rosewood (Aniba rosaeodora). The 2C value of rosewood showed a nuclear DNA content of 2.36 pg using DAPI or 2.32 pg using PI as fluorochromes.…”
Section: Flow Cytometry Analysis and Dna Quantificationmentioning
confidence: 70%